PENERAPAN MODEL PROTOTYPE UNTUK PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PEMBERIAN PAKAN IKAN BERDASARKAN FOOD CONVERSION RATIO (FCR) - Muldani Rachmat, Imam Fauzy (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2024)
Efficient feed management is crucial for successful fish farming. Improper feed management leads to waste, poor water quality, fish mortality, reduced yields, and decreased operational efficiency. A primary challenge is determining appropriate feed rations based on fish growth stages. This research developed a web-based information system to aid fish farmers in efficient and accurate feed management. The system calculates feed rations using a formula based on fish biomass and incorporates feed efficiency analysis via the Food Conversion Ratio (FCR). A Prototype Model was used for system development due to its adaptability to user feedback. Results show the system automatically calculates feed rations, manages fish sampling data, analyzes feed efficiency using FCR, and generates daily reports for efficient feed management. Field trials validated the system's effectiveness, demonstrating its ability to provide information on feed efficiency and reduce feed waste.